Frankenstein - Shelly, Mary. (Oxford : Oxford University Press, 2008)
Classics, modern fiction, non-fiction and more. Written for secondary and adult students the Oxford Bookworms Library has seven reading levels from A1-C1 of the CEFR.Victor Frankenstein thinks he has found the secret of life. He takes parts from dead people and builds a new ''man''. But this monster is so big and frightening that everyone runs away from him - even Frankenstein himself! The monster is like an enormous baby who needs love. But nobody gives him love, and soon he learns to hate. And, because he is so strong, the next thing he learns is how to kill...
Level 3.
Keywords: Readers (Adult); Reading comprehension -- Problems, exercises, etc; English language -- Textbooks for foreign speakers; Frankenstein, Victor (Fictitious character) -- Fiction; Frankenstein's monster (Fictitious character) -- Fiction